2014
DOI: 10.1158/2159-8290.cd-13-0617
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Landscape of Clinical Resistance to RAF Inhibition in Metastatic Melanoma

Abstract: Most patients with BRAFV600 metastatic melanoma develop resistance to selective RAF kinase inhibitors. The spectrum of clinical genetic resistance mechanisms to RAF inhibitors and options for salvage therapy are incompletely understood. We performed whole exome sequencing on formalin-fixed, paraffin embedded (FFPE) tumors from 45 patients with BRAFV600 metastatic melanoma who received vemurafenib or dabrafenib monotherapy. Genetic alterations in known or putative RAF inhibitor resistance genes were observed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
730
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 820 publications
(762 citation statements)
references
References 53 publications
22
730
1
9
Order By: Relevance
“…The elucidation of secondary mechanisms of resistance to BRAF-directed therapies has generated a substantial literature 115 , although larger datasets and meta-analyses have revealed that only a handful of changes underlie the preponderance of genomic resistance mechanisms. In the largest studies to date 20,[116][117][118] , involving 132 samples obtained at the time of clinical resistance, one or more genomic causes of resistance were identified in 58% of patients: NRAS/KRAS mutation in 20%, BRAF splice vari ants in 16%, BRAF amplification in 13%, MEK1/2 mutation in 7%, and non-MAPK-pathway alterations in 11%. Similar resistance mechanisms have been described with combined BRAF-MEK inhibition 119,120 .…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%
“…The elucidation of secondary mechanisms of resistance to BRAF-directed therapies has generated a substantial literature 115 , although larger datasets and meta-analyses have revealed that only a handful of changes underlie the preponderance of genomic resistance mechanisms. In the largest studies to date 20,[116][117][118] , involving 132 samples obtained at the time of clinical resistance, one or more genomic causes of resistance were identified in 58% of patients: NRAS/KRAS mutation in 20%, BRAF splice vari ants in 16%, BRAF amplification in 13%, MEK1/2 mutation in 7%, and non-MAPK-pathway alterations in 11%. Similar resistance mechanisms have been described with combined BRAF-MEK inhibition 119,120 .…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%
“…We sequenced 80 patient tumors by WES or by targeted sequencing with a panel of 40 melanoma driver genes and genes known to be drivers of resistance to targeted therapy (Supplementary Table S4; refs. [30][31][32]. Forty-eight tumors carried V600 BRAF mutations and one a K601 mutation ( Fig.…”
Section: Identifi Cation and Validation Of Treatments For Non-v600 Mumentioning
confidence: 99%
“…We advocate that BRAF and NRAS ctDNA are monitored and further validated in prospective clinical trials and they now have a part in routine clinical practice. With targeted therapies, an increase in BRAF -mutant VAF will provide an early warning of progression, and the NRAS analysis will reveal mechanisms of resistance in approximately 30% of patients ( 32 ). In particular, on May 10, 2018.…”
Section: I I I I I I I I I I I I I I I I I I I I I I I I I Imentioning
confidence: 99%
“…However, there is significant variability in the magnitude of the initial response (37,38), and most of the cases develop robust drug resistance after six months of treatment (39), despite the fact that no genetically resistant subclones have been detected before treatment, even in tumors that show modest responses. Further, different genetic resistance mechanisms can develop in the same patient (40), often at multiple metastatic sites (41). It is therefore suspected that certain extrinsic mechanisms underlie and determine the initial response, following the adaptation and acquisition of genetically robust drug resistance.…”
Section: Application To Intravital Imagingmentioning
confidence: 99%